Pemanfaatan Media Wordwall terhadap Evaluasi Pembelajaran Matematika di Sekolah Dasar - Annisaul Mutmainnah; Refiona Andika (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
This research is motivated by the lack of utilization and use of digital-based learning media and less varied learning media. This research aims to develop learning media using Wordwall where students will learn based on media that has been validated and has been categorized as valid, practical, and effective. The type of research carried out is Research and Development (R&D) using the ADDIE model which has 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. Data was obtained based on a validation questionnaire of material experts, linguists, and media experts; questionnaire on the practicality of teacher and student responses; and the effectiveness of the results of the student evaluation test. The results of the material validity test in the development of learning media using Wordwall obtained a percentage result of 93.33% with a very valid category, a language validity test result of 96% with a very valid category, and a media validity result of 86.71% with a very valid category. Meanwhile, the results of the practicality test obtained a percentage of 91.25% with the category of very practical for the teacher response questionnaire and 94.66% for the student response questionnaire with the category of very practical and the results of the effectiveness test obtained a percentage result of 93.35% with the category of very effective. Thus, it can be concluded that learning media using Wordwall in grade IV Mathematics learning in elementary schools has been proven to be valid, practical, and effective in the learning process.